PVC additives : performance, chemistry, developments, and sustainability - Schiller, Michael (Hanser Publishers, 2015)
PVC differs in its stabilization compared to other commodity plastics. Various metal compounds are suitable for the stabilization of PVC: lead, tin, calcium, magnesium, zinc, rare earths, and also almost-metal-free systems. These differences are described in the introductory part of this book, with their advantages, possibilities, and problems, from the perspective of the chemist but made understandable for salespeople and technicians. Numerous tables and figures are included, providing structures and physico-chemical data. A special section for beginners is dedicated to guiding formulations and test methods. A relatively short section deals with development trends in Europe. Sustainability is a major theme, and it is demonstrated that PVC has a strong potential to develop into a fully sustainable material.